Laser texturing of piston ring for tribological performance improvement - Rita Ferreira; Óscar Carvalho; Luís Sobral; Sandra Carvalho; Filipe Silva (Friction, 2023)
Abstract The radial surface coating layer of compression piston rings is used to improve their wear resistance during the internal combustion engine operation. However, at top dead centers, the friction coefficient of the piston ring-cylinder liner pair is detrimental to the engine’s tribological performance. In this work, dimples with different texture dimensions and densities were tested in a home-developed tribometer. The friction coefficient was measured for all samples, and for those with the best results, their wear resistance was assessed. The texture with an aspect ratio of 0.25 and a density area of 15% reported the best tribological results.